Modified Organized Systems by Incorporation of Carbon Allotropes and Derivatives for Electron Shuttle, ET, FRET, MEF, and Quantum Biology Coupling - García Quismondo, E.; Bracamonte, A. Guillermo (2024)
Fil: García Quismondo, E. IMDEA Energy. Electrochemical Processes Unit, España.